Virtual Instrument for a Multi-illumination Dome System - M. A. Khanesar; H. Corcoran; L. MacDonald; V. Pawar; S. Robson; S. Piano (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
A virtual instrument has been developed to study a multi-illumination dome system on digital objects using a camera mounted on top of the dome. The reliability of the blender environment is investigated for simulating the functions of components of this system. The high-precision three-dimensional (3D) mesh of an object measured with a laser tracker equipped with an AS1 scanner is used as a digital object within this virtual instrument. The camera is modelled by both intrinsic and extrinsic parameters and the virtual lights by power, beam angle and diffusion. The parameters are adjusted to match the real camera and light sources. The surface normals estimated using images taken of the 3D digital object using different illumination conditions are compared against actual surface normals for three artefacts with fully determined surface normals. Results show that the three sets of surface normals match each other and the mean value of the angles between the sets of surface normals for least squares with a threshold approach is limited to a few degrees for the case of objects of a few centimeters in size. Inspired by the results of surface normal estimation for the three digital artefacts, the same algorithms are then applied to a digital object scanned using a laser scanner.